Experimental and theoretical investigations on magnetic and related properties of ErRuSi. (19th March 2015) - Gupta, Sachin; Das, A; Suresh, K G; Hoser, A; Knyazev, Yu V; Kuz'min, Yu I; Lukoyanov, A V
Abstract: We report experimental and theoretical studies of magnetic and related properties of ErRuSi compound. Various experimental techniques such as neutron diffraction, magnetization, magneto-thermal, magneto-transport, optical conductivity have been used to investigate this compound. Neutron diffraction shows ferromagnetic ordering at low temperatures with moments aligned in the ab plane. Neutron diffraction and magnetization data indicate the influence of crystalline electric field effects in the moment at low temperatures. The compound shows good magnetocaloric properties with a low-field adiabatic temperature change of 4.7 K, which is larger than that of many proposed low temperature magnetic refrigerant materials. Magnetoresistance (MR) shows large negative value at 8 K, which changes its sign and increases in magnitude with decrease in temperature and/or increase in field. The positive MR at low temperatures is attributed to the Lorentz force effect. The electronic structure calculations accounting for electronic correlations of the 4 f electrons of Er elucidate the ferromagnetic ordering and effective paramagnetic moment. Interband transitions between the Ru and the Er d states and the Er f states in one spin projection are found to form the main feature of the measured optical conductivity in this compound.